Scientific or regulated validation: a tiered approach? Meeting report from a joint EBF/DVDMDG workshop. (August 2015) - Timmerman, Philip; Lowes, Steve; McDougall, Stuart; Colligon, Irina; Miksic, Joy; Chowdhury, Swapan; White, Steve; Aubry, Anne-Françoise; Jenkins, Rand; Kemper, Christopher
Tiered approach is rapidly gaining interest in the regulated bioanalytical community. Alternative approaches to the workflows as proposed in the regulatory Guidance (US FDA, EMA) are being used in discovery and early drug development, but with a growing array of assay types and studies requiring bioanalytical support in early drug development, the bioanalytical community is discussing how to bring best value to support these studies. Recently, international industry groups like European Bioanalysis Forum and Global Bioanalysis Consortium have discussed and published on the opportunity and need to include tiered approach more systematically in the early drug development support. On the back of these discussions, the Delaware Valley Drug Metabolism Discussion Group together with the European Bioanalysis Forum organized a meeting in Langhorne (PA, USA) to discuss the hurdles and added value of tiered approach with stakeholders from the Bioanalysis, quality assurance and PK community. The discussions focused on proposing scientific validation for studies where there is currently a mixed use of regulatory and tiered approach workflows. The meeting was well attended and the presentations and panel discussions contributed to a better understanding of what the industry is proposing as future practice.